(untitled) (Journal of Special Education and Rehabilitation, 2014)
Many studies tested the association between numerical magnitude processing and mathematical achievement with conflicting findings reported for individuals with mathematical learning disorders. Some of the inconsistencies might be explained by the number of non-symbolic stimuli or dot collections used in studies. It has been hypothesized that there is an object-file system for ‘small’ and an analogue magnitude system for ‘large’ numbers. This two-system account has been supported by the set size limit of the object-file system (three items). A boundary was defined, accordingly, categorizing numbers below four as ‘small’ and from four and above as ‘large’. However, data on ‘small’ number processing and on the ‘boundary’ between small and large numbers are missing. In this contribution we provide data from infants discriminating between the number sets 4 vs. 8 and 1 vs. 4, both containing the number four combined with a small and a large number respectively. Participants were 25 and 26 full term 9-month-olds for 4 vs. 8 and 1 vs. 4 respectively. The stimuli (dots) were controlled for continuous variables. Eye-tracking was combined with the habituation paradigm. The results showed that the infants were successful in discriminating 1 from 4, but failed to discriminate 4 from 8 dots. This finding supports the assumption of the number four as a ‘small’ number and enlarges the object-file system’s limit. This study might help to explain inconsistencies in studies. Moreover, the information may be useful in answering parent’s questions about challenges that vulnerable children with number processing problems, such as children with mathematical learning disorders, might encounter. In addition, the study might give some information on the stimuli that can be used to effectively foster children’s magnitude processing skills.